Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Find the solution to $$a_n = 5a_{n−2} − 4a_{n−4}$$ with $$a_0 = 3$$ $$a_1 = 2$$ $$a_2 = 6$$ $$a_3 = 8$$

My answer: Observe that the degree of recurrence is 4. Hence, the characteristic equation is: $x^4 - 5x^2 +4 = 0$. Solving for $y=x^2$ we get $y_1=1$, $y_2 = 4$. Hence, the solutions are $x_1 = -1$, $x_2 = 1$, $x_3 = -2$, $x_4 = 2$. This implies that $a_n = \alpha_1(-1)^n + \alpha_2 + \alpha_3 (-2)^n + \alpha_4(2^n)$. It remains to solve the initial conditions for $\alpha_i-s : \alpha_1 = 1, \alpha_2 = 1, \alpha_3 = 0, \alpha_4 = 1$.

Where should I go from here to ensure the answer is fully answered and complete? Thank you!

share|improve this question
1  
I think you're going to need to correct some subscripts in your relation in order to clarify this problem. (Thank you.) –  RecklessReckoner Apr 15 '13 at 0:17
    
What subscripts? –  stevenmadden Apr 15 '13 at 0:18

2 Answers 2

Since the recurrence relation is linear, the general solution is a linear combination of 4 particular solution you found. Initial conditions determine unknown constants: $$ a_n = \alpha_1 + \alpha_2 (-1)^n + \alpha_3 2^n + \alpha_4 (-2)^n $$ Now substitute initial conditions for $n=0$, $n=1$, $n=2$ and $n=3$ to find $\alpha_1$, $\alpha_2$, $\alpha_3$ and $\alpha_4$.

share|improve this answer
    
Hmm where did you get that equations for $a_n$ ? –  stevenmadden Apr 15 '13 at 0:21
    
I edited and fixed the original question and answer. Could you just make sure it's fixed in your answer as well? Thanks! –  stevenmadden Apr 15 '13 at 0:24

Just for kicks, use generating functions on this one. Define $A(z) = \sum_{n \ge 0} a_n z^n$. Your recurrence is: $$ a_{n + 4} = 5 a_{n + 2} - 4 a_n \quad a_0 = 3, a_1 = 2, a_2 = 6, a_3 = 8 $$ Using properties of ordinary generating afunctions: $$ \frac{A(z) - a_0 - a_1 z - a_2 z^2 - a_3 z^3}{z^4} = 5 \frac{A(z) - a_0 - a_1 z}{z^2} - 4 A(z) $$ Solving for $A(z)$, written as partial fractions: $$ A(z) = \frac{1}{1 - z} + \frac{1}{1 + z} + \frac{1}{1 - 2 z} $$ Expanding the geometric series: $$ a_n = 1 + (-1)^n + 2^n $$

share|improve this answer
    
So my answer is correct? –  stevenmadden Apr 15 '13 at 0:35
    
Still not sure lol –  stevenmadden Apr 15 '13 at 1:25
    
@jtm22, check yourself if all the developments agree and if the results are the same... –  vonbrand Apr 15 '13 at 2:40

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.